Dean, Fred (audio interview #6 of 6) - Dean, Fred (10/24/1897 - 12/1/1983); Asher, Bonnie, interviewer
INTERVIEW DESCRIPTION - This is the final interview and it was conducted in Dean's Long Beach home. 6/1/1982